Healthcare system simulation using witness - Wong, Kuan Yew (2013)
Simulation techniques have a proven track record in manufacturing industry as well as other areas such as healthcare system improvement. In this study, simulation model of a health center in Malaysia is developed through the application of WITNESS simulation software which has shown its flexibility and capability in manufacturing industry. Modelling procedure is started through process mapping and data collection and continued with model development, verification, validation and experimentation. At the end, final results and possible future improvements are demonstrated.